Discussion on technical solutions to fibre-optic home networking - Zhiyong MA (Dianxin kexue)
Technical solutions for fibre-optic home networking, including ITU-T standard G.hn, PON access networks, and IEEE fibre-optic Ethernet, were introduced, and they were analyzed and compared from the aspects of technical characteristics, standardization, industrial chain, future development, etc.Proposals on home gateway location and drop fibre cable termination were also given, and the experiment results show that the proposed solution can improve the Wi-Fi coverage of the home gateway and the wireless access rate.